Analysis of Factors Affecting the Performance of Midwifery Workers in the Work Area of the Siborong Borong Health Center, North Tapanuli Regency - Lastaria Lumbanraja; Megawati Megawati; Yuniati Yuniati (Journal La Medihealtico, 2022)
One of the programs to reduce MMR in Indonesia is to improve the quality of health services, especially health services for pregnant women by professionals in accordance with Antenatal Care (ANC) service standards. One of the causes of the high maternal mortality rate in Indonesia is pregnant women who are at risk of not being detected early. The purpose of the study was to analyze the performance determinants of midwifery workers in the working area of the Siborong Borong Health Center, Siborong Borong District, North Tapanuli Regency.The research design used in this study was an analytic survey with a cross sectional design. The population in this study were all midwifery workers who worked at the Siborong Borong Health Center, Siborong Borong District, North Tapanuli Regency, as many as 62 midwifery workers, from July to September 2021. The number of samples to be studied was 62 people. Data analysis was carried out by univariate, bivariate and multivariate analysis. The statistical test used is the chi square test and logistic regression. The results of the chi square test show that the variables of leadership, motivation, discipline, incentives and work environment have a p-value of 0.001 < 0.05, meaning that leadership, motivation, discipline, incentives and work environment affect the performance of midwives at the Siborong Borong Health Center. The conclusion of the multiple logistic regression test shows that the leadership variable with an odds ratio (OR) of 47.802 is more dominant in influencing the performance of midwifery workers.